Prognosticating Factors of Relapse in Clubfoot Management by Ponseti Method. Issue 10 (November 2018) - Zhao, Dahang; Li, Hai; Zhao, Li; Kuo, Ken N.; Yang, Xuan; Wu, Zhenkai; Liu, Jianlin; Zhu, Jie
Abstract : Background: It is challenging that some Ponseti method corrected clubfeet have a tendency to relapse. Controversies remain as to the implication of initial severity, representing the deformity degree, as well as number of casts needed, representing the treatment process, in predicting relapse. However, no study has been reported to take these 2 parameters into comprehensive consideration for outcome measurement. The purpose of this study is to investigate the correlation between the initial Pirani score and the number of casts required to correct the deformity in our series; to evaluate noncompliance as a risk factor of the deformity recurrence in Ponseti treatment; to test the validity and predictive value of a new proposed parameter, ratio of correction improvement (RCI) which is indicated by the initial Pirani scores divided by the number of casts. Methods: A total of 116 consecutive patients with 172 idiopathic clubfeet managed by Ponseti method were followed prospectively for a minimum of 2 years from the start of brace wearing. RCI value and the other clinical parameters were studied in relation to the risk of relapse by using multivariate logistic regression analysis modeling. Results: A positive correlation between the initial Pirani score and the number of casts required to correct the deformity was found in our series ( r =0.67, P <0.01). There were 45 patients (39%) with brace noncompliance. The relapse rate was 49% (22/45). The odds ratio of relapse in noncompliant patients was 10 times more that in compliant patients (odds ratio=10.30 and 95% confidence interval, 2.69-39.42; P <0.01). The multivariate logistic regression analysis showed that there was significant association between relapse and RCI value. There were 42 patients (36%) with RCI value <1, among them, the relapse rate was 57% in 24 patients. The odds ratio of relapse in patients with RCI value <1 was 27 times more likely to relapse than those >1 (odds ratio=26.77 and 95% confidence interval, 5.70-125.72; P <0.01). Conclusions: On the basis of the findings from our study, we propose the RCI to be a new parameter in predicting the risk of relapse in Ponseti method of clubfoot management. Early intervention is recommended to optimize the brace compliance particularly in case with lower RCI value. Level of Evidence: Level II—prognostic. Abstract : Supplemental Digital Content is available in the text.